The Next Phase of Chemoprevention Research - Cohen, Ezra E.W.; Schilsky, Richard L. (Cancer prevention research (Philadelphia, Pa.), 2011)
Phase 0 clinical trials are meant to explore mechanism of action, pharmacokinetics, pharmacodynamics, or biodistribution of investigational compounds in an efficient manner with relatively few subjects. Phase 0 designs have been applied sparingly in cancer research, but this issue of the journal provides an example of their utility reported by Reid and colleagues (beginning on page 347). Indeed, aspects of the phase 0 design lend themselves well to chemoprevention research, suggesting that this approach will become more common in the near future. Cancer Prev Res; 4(3); 293–5. ©2011 AACR.